Analysis of the structure of health benefits of the Hospital Emergency Ward at the Public University Hospital No. 4 in Lublin - Rudnicka-Drożak, Ewa; Wieczorski, Marcin; Rybojad, Beata; Krawczyk, Wojciech (Polish Journal of Public Health, 2009)
Introduction. The Hospital Emergency Ward (Polish SOR) is the institutional and organizational structure of emergency medicine and it is fundamental and decisive for functioning of the medical emergency system in Poland. Aim. The aim of the study was the analysis of the structure of health benefits offered by the Hospital Emergency Ward at the Public University Hospital No. 4 in Lublin. Material and methods. The analysis of medical documentation including a year period (01.01.2008-31.12.2008) of the Emergency Ward of Public University Hospital No. 4 in Lublin was used in this study. Results. Findings point to the fact that in the examined period the most health benefits were offered in General Admissions Room – 11 237 consultations at an outpatients’ clinic and there were 18 317 hospitalizations. Most of the consultations were emergency and took place in General Admissions Room – 99.46%. Conclusion. It is alarming that majority of the clinical consultations in General Admissions Room and Traumatic-Surgical Department were given at the time of the primary and specialist health care units operation.